DbLGL: an online leukemia gene and literature database for the retrospective comparison of adult and childhood leukemia genetics with literature evidence. (21st June 2018) - Liu, Yining; Luo, Mingyu; Jin, Zhaochen; Zhao, Min; Qu, Hong
Abstract: Leukemia is a group of cancers with increased numbers of immature or abnormal leucocytes that originated in the bone marrow and other blood-forming organs. The development of differentially diagnostic biomarkers for different subtypes largely depends on understanding the biological pathways and regulatory mechanisms associated with leukemia-implicated genes. Unfortunately, the leukemia-implicated genes that have been identified thus far are scattered among thousands of published studies, and no systematic summary of the differences between adult and childhood leukemia exists with regard to the causative genetic mutations and genetic mechanisms of the various subtypes. In this study, we performed a systematic literature review of those susceptibility genes reported in small-scale experiments and built an online gene database containing a total of 1805 leukemia-associated genes, available at http://soft.bioinfo-minzhao.org/lgl/ . Our comparison of genes from the four primary subtypes and between adult and childhood cases identified a number of potential genes related to patient survival. These curated genes can satisfy a growing demand for further integrating genomics screening for leukemia-associated low-frequency mutated genes. Database URL: http://soft.bioinfo-minzhao.org/lgl/